192k views
4 votes
G(x) = x2 − 5x
h(x)= 4x + 4
Find (g ◦ h) (x)

User Bers
by
5.9k points

1 Answer

5 votes

Answer:

(g ◦ h) (x) = 16x² + 12x -4

Explanation:

We have

g(x) = x² − 5x

h(x)= 4x + 4

(g ◦ h) (x) = g(h(x))

h(x) = 4x + 4

g(h(x)) = g(4x + 4)

= (4x + 4)² - 5(4x+4) //substitute 4x + 4 wherever there is an s-term in

(4x + 4)² = 16x² + 32x + 16

5(4x + 4) = 20x + 20

(4x + 4)² - 5(4x+4) = 16x² + 32x + 16 -(20x + 20)

= 16x² + 32x + 16 - 20x - 20

= 16x² +(32x - 20x) + (16-20)

= 16x² + 12x -4

User JTaub
by
5.4k points